ANALISIS TINGKAT MISKONSEPSI SISWA MAN BINJAI PADA MATERI SUHU DAN KALOR MENGGUNAKAN THREE-TIER MULTIPLE CHOICE DIAGNOSTIK TEST - Suhaila, Aninda; Sani, Ridwan Abdullah; Azhar, Zul (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
Development of a Three-Tier Multiple Choice Diagnostic Test to determine the level of misconceptions of SMA/MA students regarding temperature and heat.The use of a three-tier multiple choice diagnostic test instrument can determine the level of student misconceptions. This research and development aims to determine the level of student misconceptions regarding temperature and heat material. This research is R&D research with a 4D development model. This research used 3 validators and 30 research subjects in class XII MIA 2 MAN Binjai. The percentage of students who experienced the most misconceptions was 90% in question 10. The average percentage of students who experienced misconceptions was 58.2%. Based on the results obtained, the three-tier multiple choice diagnostic test instrument developed was effective in determining the level of misconceptions experienced by students regarding temperature and heat material so that the questions could be distributed.